2001
DOI: 10.1021/jf000595h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Volatiles, Phenolics, Sugars, Antioxidant Vitamins, and Sensory Quality of Different Colored Carrot Varieties

Abstract: Four different colored carrots, orange, purple with orange core, yellow, and white, were examined for their content of phenolics, antioxidant vitamins, and sugars as well as their volatiles and sensory responses. A total of 35 volatiles were identified in all carrots, 27 positively. White carrot contained the highest content of volatiles, followed by orange, purple, and yellow. In total, 11, 16, 10, and 9 phenolic compounds were determined for the first time in orange, purple, yellow, and white carrots, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
257
5
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(305 citation statements)
references
References 40 publications
31
257
5
12
Order By: Relevance
“…Recent studies have confirmed that phenolic acid prevent coronary heart disease, cancer, inflammation, and diabetes. Hydroxycinnamic acid and its derivatives (e.g., coumaric, caffeic, ferulic and sinapic acids) are important pharmaceuticals molecules used as drugs for high blood pressure, stroke prevention, and possess antitumor activity [1][2][3]. There are three possible isomers of coumaric acid which differ in the position of the hydroxyl group substitution on the phenyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that phenolic acid prevent coronary heart disease, cancer, inflammation, and diabetes. Hydroxycinnamic acid and its derivatives (e.g., coumaric, caffeic, ferulic and sinapic acids) are important pharmaceuticals molecules used as drugs for high blood pressure, stroke prevention, and possess antitumor activity [1][2][3]. There are three possible isomers of coumaric acid which differ in the position of the hydroxyl group substitution on the phenyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in carotenoid profile has been reported with some carrot cultivars primarily accumulating lutein whilst others primarily accumulated a and 1 carotene [157]. Levels of individual polyacetylenes differ between different carrot varieties [4,30,34,62,79,105,106], and between different members of the Apiaceae family [38,192]. In an analysis of 5 members of the Apiaceae, falcarinol was found in all investigated taxa except parsley.…”
Section: Crop and Cultivarmentioning
confidence: 99%
“…Amongst the cultivated species levels of falcarinol were higher in chervil (Anthriscus cerefolium), dill (Anethum graveolens) and parsnip (Pastinaca sativa) [38]. Levels of carotenes, phenolics, and antioxidant capacity are reported as higher in purple carrot varieties than in other varieties [4,168]. In a field study of 27 carrot varieties grown under uniform cultural conditions levels of falcarinol ranged from 0.70 to 4.06 mg/1 00g FW [136].…”
Section: Crop and Cultivarmentioning
confidence: 99%
“…Carrot roots are a good source of bioactive compounds: carotenoids, especially β-carotene and lutein, dietary fibre (pectins) as well as polyphenolic compounds (Arscott and Tanumihardjo 2010). Therefore, carrot can be an important vegetable in preventive nutrition (Alasalvar et al 2001). The level of particular bioactive compounds in carrot varies depending on many factors, i.e.…”
Section: Introductionmentioning
confidence: 99%